Nomograms for Predicting Cancer-Specific and Overall Survival Among Patients With Endometrial Carcinoma: A SEER Based Study - Zhu, Lingping; Sun, Xiaoming; Bai, Wenpei (Frontiers in Oncology, 2020)
Background: This study aimed to develop a detailed survival prognostication tool based on various clinical indicators of patients because of the lack of comprehensive prognostic tool. Methods: Data regarding 63,729 patients with endometrial cancer were extracted from the SEER database between 1988 and 2015. Univariate and multivariate Cox regression analyses were used to screen for meaningful independent prognostic factors. These factors were used to construct a nomogram model, a survival prognostication tool for 3- and 5-year tumor-specific survival and overall survival among patients with endometrial cancer. Results: A total of 63,729 patients were randomly assigned to the training group (n=42,486) and the test group (n=21,243). Age, race, year of diagnosis, histologic grade, clinical stage, and tumor size were assessed as predictors of cancer-specific survival (CSS) and univariate and multivariate Cox regression analyses were used to identify independent prognostic factors (P<0.05). Finally, a nomogram was constructed. the predicted C-indices for cancer-specific survival and overall survival training groups were 0.859 (95% confidence interval 0.847–0.871) and 0.782 (95% confidence interval 0.772–0.792). Conclusions: Nomograms constructed using various clinical indicators can provide better and more accurate predictions for patients with endometrial cancer. Those nomograms could help identify patients with high-risk endometrial cancer.